Non‐classical crystallization of very high magnesium calcite and magnesite in the Coorong Lakes, Australia. Issue 5 (24th March 2022) - Raudsepp, Maija J.; Wilson, Siobhan A.; Morgan, Bree; Patel, Avni; Johnston, Scott G.; Gagen, Emma J.; Fallon, Stewart J.
Abstract: The Coorong Lakes, South Australia, are one of the models for unravelling the 'Dolomite Problem'. Critically, today only a few modern environments remain where large quantities of very high magnesium calcite (VHMC; Ca0.5 Mg0.5 CO3 ; also described as protodolomite or disordered dolomite) and magnesite (MgCO3 ) precipitate. Previously conducted laboratory studies demonstrate that carbonate minerals can precipitate via classical and non‐classical crystallization pathways. This study uses the preserved crystal sizes, morphologies and microstructures of Ca–Mg carbonates in the Coorong Lakes (Milne Lake, Pellet Lake and North Stromatolite Lake) to evaluate which crystallization pathway most likely occurred. In the fine‐grained sediments of these lakes, very high magnesium calcite and magnesite occur as aggregate particles of nanocrystals (<100 nm). Rietveld refinements using X‐ray diffraction data give modelled Lvol –IB crystallite size values of <120 nm for all carbonates. Transmission electron microscopy shows that, within VHMC and magnesite particles, nanocrystals have an almost identical orientation of their crystal lattice fringes. This is morphologically similar to Ca–Mg carbonates formed via an amorphous carbonate precursor in non‐classical crystallization laboratory experiments. Precipitation of carbonate minerals via an amorphous‐to‐crystalline pathway requires the water to be supersaturated relative to both crystalline and amorphous phases. In the Coorong Lakes, surface water likely only becomes supersaturated relative to amorphous carbonate phases in the late summer after extensive evaporation. Observations suggest that VHMC and dolomite do not directly precipitate from bulk modern seawater, despite oversaturation relative to the crystalline phases, because seawater is undersaturated with respect to amorphous calcium magnesium carbonate, thus limiting the precipitation through a non‐classical crystallization pathway.